The ambivalent effect of complexity on firm performance: A study of the global service provider industry. Issue 2 (April 2019) - Larsen, Marcus M.; Manning, Stephan; Pedersen, Torben
Abstract: Prior literature is ambivalent about whether organizational complexity has positive or negative effects on firm performance. Using rich data on global service providers, we explore this ambivalence by disentangling performance consequences of different types of organizational complexity. We show that complexity arising from the coordination of different services and operations negatively influences profit margins through increased coordination costs, whereas complexity coming from the sophistication of particular services may positively influence margins through informational advantages. We also investigate the moderating effects of process commoditization and client-specific investments. Our findings point to critical performance dilemmas facing global service providers in a highly competitive industry, and they help better differentiate performance effects of complexity at different organizational levels.